Ultrasound on Erect Penis Improves Plaque Identification in Patients With Peyronie’s Disease - Liu, Yu; Zheng, Dequan; Liu, Xiaolin; Shi, Xiaohong; Shu, Shengchun; Li, Jinbing (Frontiers in Pharmacology, 2019)
Objectives: To compare the sensitivity of identification of penile plaques in the erect and flaccid penises by ultrasound in patients with Peyronie’s disease (PD). Materials and Methods: A total of 75 PD patients were screened by palpation and ultrasonography for penile lesions in both flaccid and erect penises induced by prostaglandin E1 (PG-1) injection. Results: A total of 138 lesions were identified by ultrasound in the erect penises induced by injection of PG-1. However, only 74.6% of the lesions (103) were detectable by the palpation of the flaccid penises, and 84.1% (116) by ultrasound of the flaccid penises. The ultrasound confirmed 99 of the palpated lesions in the flaccid penises. The detection rate of lesions in drug-induced erect penises by ultrasound was significantly higher than those in the flaccid penises by the ultrasound（P < 0.01）or palpation （P < 0.0005） The type of penile lesions identified by ultrasonography included tunical thickening, calcifications, septal fibrosis, and intracavernosal fibrosis. The ratios of these lesions confirmed by ultrasound were 52.6%, 33.6%, 6.0%, and 7.8%, respectively, in the flaccid penises, and 55.8%, 28.3%, 8.7%, and 7.2%, respectively, in the erect penises. Conclusion: Drug-induced erection can be used in suspicious PD patients when penile lesion is not identified by palpation or ultrasound in the flaccid penis.